Innovation of Virtual Reality: Assistance in the Development of Tengger Heritage Journey as a Promotion of Sustainable Tourism Villages in Tosari - Diky Al Khalidy; Alfyananda Kurnia Putra; Hani Fuddin; Johandi Rahma Rafani; Aizul Haswin; Bagus Sumantri (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Tosari Village is one of the tourism-supporting villages in the Bromo Tengger Semeru National Park (TNBTS) area and already has Sanja Tosari Village as a tourist village. Based on survey, observation, and interview activities, Sanja of Tosari Village has problems promoting tourism villages that still utilize personal and community social media. In addition, the promotion of tourist villages has also not utilized virtual reality technology due to minimal capacity and accessibility. The solution to problem partners is assisting the development and application of smart tourism virtual reality as a medium for promoting sustainable tourism villages. The stages of developing smart tourism virtual reality start from data collection, processing, product development, and product results carried out by partners. This community service activity results in a virtual reality-based Tengger Heritage Journey as a promotional medium for Sanja Tosari Village. With this community service activity, the management of the tourist village has the experience and ability to develop and utilize virtual reality in tourism activities.